Enhancing soil health and tobacco productivity with different organic amendments: evidence from a 7-year field experiment - Yang, Wei; He, Biao; Li, Junying; Wang, Ziyan; Tong, Wenjie; Zhu, Bo; Xiao, Zhihua; Deng, Xiaopeng; Wang, Bin (Frontiers in Soil Science, 2025)
Long-term organic fertilization is widely advocated to counteract soil fertility decline and nutrient imbalances in tobacco cropping systems. However, systematic research comprehensively evaluating the long-term effects of different organic fertilizers on soil physicochemical properties, enzyme activity, microbial diversity, tobacco yield, and quality remains limited. A 7-year field study was conducted to compare the long-term impacts of chemical fertilizer (CF), manure (CM), straw mulching (SM), and farmyard compost of manure and straw (FM) on soil health and tobacco productivity. The soil quality index (SQI) under CM, SM, and FM treatments was 18.2%, 11.9%, and 20.7% higher, respectively, than that of the CF treatment. Similarly, CM, SM, and FM treatments increased soil ecosystem multifunctionality (EMF) by 86.3%, 80.0%, and 106.7%, respectively. CM, SM, and FM treatments increased the microbial diversity index by 4.7%, 1.5%, and 7.0%, respectively. CM, SM, and FM treatments increased soil health index by 13.2%, 1.7%, and 18.6%, respectively, through concurrent improvements in the SQI, EMF, and microbial diversity index. Furthermore, CM, SM, and FM treatments not only increased tobacco yield by 6.5%, 2.8%, and 12.9%, respectively, but also significantly enhanced the proportion of premium-grade leaves by 17.8%, 3.2%, and 28.5%, respectively. Overall, farmyard compost of manure and straw maximized the concurrent gains in soil health and tobacco yield and quality. Consequently, farmyard compost of manure and straw application emerges as the most effective strategy to concurrently maintain soil health and attain high-yield, high-quality tobacco.